Enhancement of Library Services in Cloud Computing Systems: A Comprehensive Study (LIS TODAY, 2022)
[In library and information management system, Cloud Computing plays a crucial role. The majority  of libraries have been digitized and transmitted to internet platforms through manual systems. The majority of  Cloud Computing Services have been identified and large amount of computing resources can be deployed in  minutes through it. The study's goal is to talk about how libraries may improve their services. The research has  looked into how cloud-based library services can enhance library services. The study's goals are to discover  Cloud Based Application-related Library Services, as well as to identify Cloud Based plat forms-related Library  Services. The paper presents some solutions for the problem of “How is the Library services enhanced Cloud based Library Services”. The main point of the study is to discuss objectives like, to find out Cloud Based  Applications related Library Services, to identify Cloud Based platforms related to Library Services. to identify  Cloud Base free services for Libraries. Secondary data have been used for this comprehensive study. The  services are available by Cloud Technology are as storage services. Google Drive, Mega Drive, Dropbox, I  Cloud etc. Utilizing cloud-based services, libraries may create library repositories. E-books can be saved and  shared with the appropriate users. Professional support is required for library e-book lending services, which  include numerous technical infrastructure and business process components. These elements form an ecosystem  that allows libraries to secure licenses from companies to lend eBooks. Professional support is required for  library e-book lending services, which include numerous technological infrastructure and business process  components. Another important service is OPAC sharing. The Internet can be used to share bibliographic  information. As a result, the bibliographical information of Networked Automated Libraries is elaborated by  their Online Public Assess Catalog. As a result, Cloud Computing plays an important role in improving library  and information services.]
Keywords: Cloud Computing; Cloud Technology; Library repositories; OPAC Sharing, Technological infrastructure; Bibliographical Information